Ultrazvočna diagnostika obolenj dojke - Guna, Franc (Radiology and oncology (Ljubljana), 1998)
Ultrasound diagnostics of breast is a complementary techique to clinical examination of women under 35 in whom symptoms of a breast disease have been observed, as well as to nonconclusive mammograms. With this technique it is possible to distinguish between fluid and solid formations in the breast and, to a certain degree of probability, differentiate the solid ones. While the distinction between benign and malignant changes is particulay important, the ultrasound examination allows more or less only an approximate avaluation of this distiction. Furthermore, the article deals with diagnostic algorithm, parameters and criteria for categorizing the sonographic changes.
Keywords: bolezni; Breast diseases; diagnostika; dojke; Ultrasonography; ultrazvočna diagnostika